2021
DOI: 10.1590/acb360804
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline alleviates early brain injury through regulating of ER stress and autophagy after experimental subarachnoid hemorrhage

Abstract: Purpose: Subarachnoid hemorrhage (SAH) is a common complication of cerebral vascular disease. Hydrogen has been reported to alleviate early brain injury (EBI) through oxidative stress injury, reactive oxygen species (ROS), and autophagy. Autophagy is a programmed cell death mechanism that plays a vital role in neuronal cell death after SAH. However, the precise role of autophagy in hydrogen-mediated neuroprotection following SAH has not been confirmed. Methods: In the present study, the objective was to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Studies have shown that H 2 is highly capable of penetrating the biological membranes including the BBB. Thus, this characteristic of H 2 provides unrestricted access to the CNS, causing therapeutic effects on many CNS diseases, including ischemia stroke, intracranial hemorrhage, and neurodegenerative diseases [41][42][43][44]. Moreover, previous studies have shown that administration of H 2 inhalation attenuated redox stress, inflammatory and OS mediators, and prevented BBB disruption by reducing the activation of mast cells and degranulation that result in amelioration of neurological conditions [24,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that H 2 is highly capable of penetrating the biological membranes including the BBB. Thus, this characteristic of H 2 provides unrestricted access to the CNS, causing therapeutic effects on many CNS diseases, including ischemia stroke, intracranial hemorrhage, and neurodegenerative diseases [41][42][43][44]. Moreover, previous studies have shown that administration of H 2 inhalation attenuated redox stress, inflammatory and OS mediators, and prevented BBB disruption by reducing the activation of mast cells and degranulation that result in amelioration of neurological conditions [24,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…It is a major pathway to remove senescent or damaged organelles and long-lived proteins in eukaryotic cells, and it plays a critical role in maintaining intracellular homeostasis and recycling cellular components. Recently research have been confirmed that autophagy is associated with many CNS disorders, including cerebral ischemia ( Xu et al, 2021 ), trauma ( Cui et al, 2015 ), SAH ( Jiang et al, 2021 ), and ICH ( Yuan et al, 2017 ). In our study, we confirmed that autophagy occurs in the brain after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen-enriched water has the same antioxidant, anti-inflammatory, and antiapoptotic effects as those of hydrogen inhalation. 35 Indeed, studies have emphasized that HRS has preventive and therapeutic effects in many pathologies, including aplastic anemia, 36 subarachnoid hemorrhages, 37 intestinal damage in hemorrhagic shock, 38 heart dysfunction, 20 cardiopulmonary bypass-induced cerebral damage, 39 renal damage after IR, 40 Alzheimer, 41 burn damage, 42 erythrocyte deformability after limb ischemia, 19 and postoperative cognitive function. 21 Others have demonstrated that HRS may potentially alleviate primary lung IR injury.…”
Section: Discussionmentioning
confidence: 99%